2015
DOI: 10.1016/j.bjorl.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

P300 in individuals with sensorineural hearing loss

Abstract: P300 can be recorded in individuals with severe and profound congenital sensorineural hearing loss; it may contribute to the understanding of cortical development and is a good predictor of the early intervention outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 38 publications
4
17
0
Order By: Relevance
“…P300 potential (an Event Related Potential, ERP) shows the cortical electrophysiological activity involved in attention, memory, discrimination, integration and decision making skills [7] [8]. Auditory P300 may reflect the conscious process of acoustic differences present in speech signal [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…P300 potential (an Event Related Potential, ERP) shows the cortical electrophysiological activity involved in attention, memory, discrimination, integration and decision making skills [7] [8]. Auditory P300 may reflect the conscious process of acoustic differences present in speech signal [9].…”
Section: Introductionmentioning
confidence: 99%
“…Auditory P300 may reflect the conscious process of acoustic differences present in speech signal [9]. P300 has been widely used for the evaluation of central auditory functions in people with hearing loss [8] [10] [11]. These studies report an evaluation of latency and amplitude of different ERPs (N1, P2, N2 and P300 for Polen et al; N1, N2, P300 and mismatch negativity for Oates et al and only P300 potential for Reis et al) in relation to the degree of the hearing impairment or to the complexity of the recognition tasks.…”
Section: Introductionmentioning
confidence: 99%
“…They reported the type of command, such as "pay attention to the infrequent stimulus," and "respond only to the infrequent stimulus" (17)(18)(19) . The types of tasks requested for the identification of the stimulus infrequent detected in the literature surveyed were: "mental counting" (2,3,7,9,11,20,21) ; "raising the finger" (6) ; "counting aloud" (12,22) ; "pressing the button" (23,24) and "counting and raising one hand" (25) . Although the task of "mentally counting" has been the most found in the literature, it is also the task that can cause more difficulties for the record analysis, because the patients with cognitive disorders or without evaluator effect control to the number reported at the end of the test can compromise the performance of the task or registration.…”
Section: Discussionmentioning
confidence: 99%
“…The motivation to establish a protocol for behavioral assessment and individuals follow-up with variation in the hearing system in combination with objective assessments has increasingly been emphasized in the literature, not only for individuals with hearing loss or attention disorders, but also for individuals with degenerative diseases, allowing a data comparison during the disease course, both in terms of speech, writing and auditory perception (6) . Few studies have reported normal P300 values for different age ranges compared to other diagnostic procedures, mainly regarding the parameters used for assessment and electrode positioning.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between task difficulty and prelingual deafness could not be investigated, however, because there was no control group. Reis et al 17 studied P300 latency and amplitude in 29 patients with prelingual, severe-to-profound sensorineural hearing loss (without CI), and found significant differences in latency and amplitude that were related to age and severity of hearing loss, respectively. The study had no control group and the ERP was only delivered in Cz electrode.…”
Section: Introductionmentioning
confidence: 99%